Increased sensitivity of OSHA method analysis of diacetyl and 2,3-pentanedione in air - LeBouf, Ryan (J Occup Environ Hyg, 2017)
Gas chromatography/mass spectrometry (GC/MS) operated in selected ion monitoring mode was used to enhance the sensitivity of OSHA Methods 1013/1016 for measuring diacetyl and 2,3-pentanedione in air samples. The original methods use flame ionization detection which cannot achieve the required sensitivity to quantify samples at or below the NIOSH recommended exposure limits (REL: 5 ppb for diacetyl and 9.3 ppb for 2,3-pentanedione) when sampling for both diacetyl and 2,3-pentanedione. OSHA Method 1012 was developed to measure diacetyl at lower levels but requires an electron capture detector, and a sample preparation time of 36 hours. Using GC/MS allows detection of these two alpha-diketones at lower levels than OSHA Method 1012 for diacetyl and OSHA Method 1016 for 2,3-pentanedione. Acetoin and 2,3-hexanedione may also be measured using this technique. Method quantification limits were 1.1 ppb for diacetyl (22% of the REL), 1.1 ppb for 2,3-pentanedione (12% of the REL), 1.1 ppb for 2,3-hexanedione, and 2.1 ppb for acetoin. Average extraction efficiencies above the limit of quantitation were 100% for diacetyl, 92% for 2,3-pentanedione, 89% for 2,3-hexanedione, and 87% for acetoin. Mass spectrometry with OSHA Methods 1013/1016 could be used by analytical laboratories to provide more sensitive and accurate measures of exposure to diacetyl and 2,3-pentanedione.